Agresywne zachowania językowe w sytuacji granicznej - Balowska, Grażyna (Bohemistyka, 2022)
The subject of the analysis are aggressive linguistic behaviours constituting a part of the pandemic discourse. We are interested in verbal aggression in a borderline situation, for which we consider the COVID-19 disease as the effect of the SARS-CoV-2 coronavirus. The research material comes from the discussion forums of the Czech internet portal Novinky.cz. It was collected in the period from July 2021 to August 2022. The researched comments are an example of so-called written conversation, because they reflect the nature of spontaneous communication, the texts are unprepared, created with the usage of the language of everyday communication (běžná mluva), colloquialisms, slangisms, the obecná čeština, with a clear presence of expressive vocabulary. The article discusses manifestations of verbal aggression in a lexical-pragmatic perspective, while verbal aggression is understood as any deliberate linguistic behavior that causes harm to another person, inflicts psychological discomfort, presents them in a bad light, depreciates, mocks or ridicules them. The analysis focuses on such aggressive linguistic behaviour as threats, curses, insults, ridicule, accusations.